Suitability of Using LA Abrasion Machine for the Nano Manufacturing of Palm Oil Fuel Ash and Incorporating in Mortar Mixture - Liew, Yu Xuan; Putra Jaya, Ramadhansyah; Chin, Siew Choo (Bentham Open, 2023)
Background: In order to enhance the properties of palm oil fuel ash-based mortar, researchers have explored the concept of reducing palm oil fuel ash (POFA) to a nanoscale. While previous studies have utilized ball milling machines with high grinding speed to achieve nano-scale POFA, the Los Angeles abrasion machine, which is more readily available and has a slower grinding speed, has been rarely employed. Objective: The study aimed to investigate the suitability of using a Los Angeles abrasion machine with a low grinding speed to produce nano palm oil fuel ash. This paper also provides a comparison of the effect of using the nano POFA with different particle sizes within the range of 982 to 150 nm on the mortar’s flowability and compressive strength. Methods: To produce nano-size palm oil fuel ash using the Los Angeles abrasion machine, the received palm oil fuel ash was thermally treated and ground using a Los Angeles abrasion machine with varying grinding periods. The grinding process parameters were kept constant, but second grinding periods of 50,000, 80,000, and 110,000 cycles were introduced. All three types of nano palm oil fuel ash were analyzed for their physical properties, chemical properties, morphology, and mineralogy. Furthermore, these nano palm oil fuel ashes were incorporated into a designed mortar mix along with micro palm oil fuel ash. The mortar’s fresh properties and compressive strength at different curing ages were observed and analyzed. The relationship between various factors, such as the replacement rate of micro, nano palm oil fuel ash, the grinding cycles of nano POFA, and the corresponding responses, specifically the compressive strength at different curing ages, was analyzed and explained using the response surface methodology. Results: The 110k cycle nano palm oil fuel ash had a smaller particle size of 103.1 nm, while a particle size of 529 nm and 325 nm was found in the 50k and 80k cycle nano palm oil fuel ash. In terms of the combination of micro and nano palm oil fuel ash in the mortar, increasing the dosage of nano palm oil fuel ash contributed to improvements in flow diameter and compressive strength. However, the opposite trend was observed with micro palm oil fuel ash. The optimal mix design for the combination involved using 10% micro and 2 to 3% nano palm oil fuel ash. This composition led to an improvement rate of 7.9%, 1.48%, and 4.6% in compressive strength at 7, 28, and 90 days, respectively. While, the response surface methodology’s numerical optimization also supported the use of a similar combination. However, it additionally recommended employing the 50,000-cycle nano palm oil fuel ash in the mortar for earlier curing stages, while the 110,000-cycle nano palm oil fuel ash was suggested for later curing stages. Conclusion: Los Angeles abrasion machine could be utilized to produce nano palm oil fuel ash with a particle size up to 103 nm with the aid of designed parameters. In this mortar mix design, the impact of a small variance in nano palm oil fuel ash’s particle size was trivial compared to the replacement rate of micro palm oil fuel ash on the mortar’s compressive strength.